Factors Contributing to Disordered Eating Behaviours and At-Risk of Eating Disorders among Adolescent Girls in Kelantan, Malaysia - Soo, Kah Leng (2008)
Disordered eating attitudes and behaviours, and body image disturbances are becoming more frequent among female adolescents in Eastern countries. The disordered eating behaviours such as dietary restraint (dieting) and binge eating could be the risk factors for nutritional deficiencies, and are precursors for the development of eating disorders. This study was undertaken to examine the relationships between disordered eating attitudes and behaviours with personal factors (biological, psychological and cognitive) and socio-environmental factors (parental socioeconomic status and influence of mother, peer and media) in general population of adolescent girls. A cross-sectional study was carried out among 489 secondary school girls aged 15 – 17 years (mean age = 16.2 ± 0.5 years) in Kelantan. Subjects were invited to complete a self-administered questionnaire, including Eating Attitudes Test-26 (EAT-26), Restraint Scale of Dutch Eating Behaviour Questionnaire (DEBQ-R), Binge Scale Questionnaire (BSQ), Contour Drawing Rating Scale, Rosenberg Selfii Esteem Inventory, Fear of Fat Scale and three subscales from Perceived Sociocultural Influences on Body Image and Body Change Questionnaire. Besides, subjects were evaluated on weight management knowledge and nutrition knowledge. Anthropometric (height and weight) data were also collected on each of these subjects. On average, subjects consumed 81.1% (1663 ± 482 kcal) of recommended energy intake. Almost all nutrient intakes were less than the recommended intake for Malaysian except protein (102.6%) and total vitamin A (128.7%). Mean calcium intake (307.3 ± 133.1 mg/day) was the lowest among all nutrients, which is only 30.7% of the recommended intake. Among all subjects, 3.1% were underweight, 9.8% overweight, 8.6% obese and the remainder of 78.5% were normal weight. There were 22.3% of the subjects at-risk of eating disorders. Restrained eating and binge eating was reported by 36.0% and 35.4% of the subjects, respectively. A total of 87.3% subjects were dissatisfied with their body size and 61.5% had an incorrect perception of body weight status. More than half of the subjects were concerned about their body weight (59.1%), reported feeling dissatisfied with their body weight (58.5%) and wanted to lose weight (58.3%). Logistic regression models had explained more of the variance in the restraint scores (74.2%) and the EAT-26 scores (49.8%) than in the binge scores (34.2%). The strongest significant predictor for restrained eating was weight loss intention. In addition, dietary restraint was also significantly predicted by body weight concern, fear of being fat and influences of mother to lose weight. The three significant predictors for binge eating were influences of mother, best friend and media to lose weight. Furthermore, adolescents who were at-risk of eating disorders can be predicted by restrained eating, binge eating, fear of being fat and perceived media pressure to lose weight. The model tested in this study that based on Bandura’s Social Cognitive Theory had explained a large percentage of the variance in the behavioural factors. The high predictive power of the model tested suggests that the model is applicable to the local population. So, by addressing effectively the personal and socio-environmental factors included in the model, it may be able to influence eating behaviours and prevent the onset of disordered eating among adolescents in this country. The prevalence of disordered eating attitudes and behaviours among adolescent females in Kelantan shown by this study suggests the need for multidisciplinary studies to systematically and accurately examine eating behaviours of adolescent girls in order to solve more efficiently the increased adolescent eating problems. Preventive programmes encouraging appropriate and healthy eating behaviours should be implemented and assessed.